Torsional Strain‐Independent Catalytic Enantioselective Synthesis of Biaryl Atropisomers. Issue 43 (12th September 2022) - Luo, Zhang‐Hong; Wang, Wen‐Tao; Tang, Tian‐Yi; Zhang, Sen; Huang, Fen; Hu, Dan; Tao, Ling‐Fei; Qian, Linghui; Liao, Jia‐Yu
Abstract: Catalytic asymmetric dynamic kinetic resolution of configurationally labile bridged biaryls is emerging as a powerful strategy for atropisomer synthesis. However, the reported examples suffer from an inherent challenge as the reactivity is highly dependent on the torsional strain of the biaryl substrates, which significantly narrows down the scope and hampers the application. Herein, we report our discovery and development of a torsional strain‐independent reaction between biaryl thionolactones and activated isocyanides. By employing auto‐tandem silver catalysis, a universal synthesis of both tri ‐ and tetra ‐ ortho ‐substituted thiazole‐containing biaryls was realized in high yields with high enantioselectivities. In addition, these products could be facilely converted to a novel type of bridged biaryls bearing an eight‐membered lactone. Mechanistic studies were carried out to elucidate the cause of this unusual torsional strain‐independent reactivity. Abstract : A torsional strain‐independent reaction between biaryl thionolactones and activated isocyanides is reported. Under auto‐tandem silver catalysis, both tri ‐ and tetra ‐ ortho ‐substituted biaryls were obtained in high yields and enantioselectivities. These products could be converted to bridged biaryls bearing an eight‐membered lactone. Mechanistic studies provided key insights into the cause of this unusual torsional strain‐independent reactivity.